Variation in quantitative yield and hypericin content of St. John's wort., Hypericum perforatum L. - H Naghdi Badi; SA Ziai; MH Mirjalili; M Ahvazi; F Khalighi Sigaroodi; B Habibi Khaniani; A Farahani (Institue of Medicinal Plants, ACECR, 2004)
St John's wort, Hypericum Perforatum L. (Culsiaceae) is an important medicinal plant, which has different bioactive constituents and hypericin (a naphtodianthrone) is one of this compounds. Hypericin has many pharmacological effects such as antidepressant, antiviral and antibacterial, which cause to high production and consumption. It has known that region and genetic (accession) have significant effects on yield and content of active constituents of this plant. Because of existing 5 accessions in gene bank of medicinal plants Institute -ACECR, this study has been conducted in order to determination the best accession and evaluation role of genetic and environment on quantitative yield and hypericin content. This study has been done in research farms of medicinal plants Institute - ACECR along 1999- 2002. The experimental design was a randomized complete block with a split-plot arrangement. The parameters are measured in this study included: dry and wet herbage, content of hypericin, plant height and diameter in flowering stage. Combined analysis of variance indicated that genetic (accession) had significant effect on wet herbage (p<0.05), dry herbage, plant height & diameter (p<0.01) but had not significant effect on hypericin content. Environmental conditions (years) affected on hypericin content (p<0.01). Therefore accession and environment have main roles in production of medicinal parts and hypericin content in this plants, respectively. They could be considered as two key factors for an economically successful cultivation.